Forging A New Nation: The Role of Youth Radicalism in Semarang’s Revolutionary Struggle, 1945-1947 - Dwi Mulyatari; Abdurakhman; Raisye Soleh Haghia; Syahidah Sumayyah Rahman (Paramita: Historical Studies Journal, 2025)
Abstract: This study examines the youth resistance movement in Semarang in the early days of the Indonesian Revolution, especially between 1945 and 1947, against the Japanese and Allied armies. The youth resistance movement is characterized by a militant and radical nature, which is influenced by various factors from the past experiences of the youth. In addition to the impact of the Japanese occupation, ideological factors such as Socialism, Communism, Islam, and Nationalism also played an important role in encouraging youth radicalism in Semarang. Research on the radical youth movement in Semarang during the Indonesian Revolution is still limited, with some studies highlighting events such as the 'Five-Day Battle'. This research contributes to the understanding of the youth militant movement in Semarang through a literature review from contemporary newspaper sources published in Jakarta and Semarang as well as other related literature collections. These sources are obtained from the National Library and libraries in the local area. The results of the study show that several factors affect radicalism and youth militancy in Semarang. First, their strong motivation and purpose to resist the occupation of the Japanese army and the return of the Allies. Second, the results of Japanese education for youth through military and semi-military organizations during the Japanese occupation that strengthened the military mentality. Third, the influence of the socialist-Marxist youth group organization that developed since the time of the national movement, thus making the city of Semarang known as a "red" city.   Abstrak: Studi ini menelaah gerakan perlawanan pemuda di Semarang pada masa awal Revolusi Indonesia, khususnya antara tahun 1945 hingga 1947, terhadap tentara Jepang dan Sekutu. Gerakan perlawanan pemuda tersebut ditandai dengan sifat militan dan radikal, yang dipengaruhi oleh berbagai faktor dari pengalaman masa lalu para pemuda. Selain dampak pendudukan Jepang, faktor ideologis seperti Sosialisme, Komunisme, Islam, dan Nasionalisme juga berperan penting dalam mendorong radikalisme pemuda di Semarang. Penelitian tentang gerakan radikal pemuda di Semarang pada masa Revolusi Indonesia masih terbatas, dengan sebagian studi hanya menyoroti peristiwa seperti ‘Pertempuran Lima Hari’. Penelitian ini berkontribusi pada pemahaman tentang gerakan militan pemuda di Semarang melalui kajian literatur dari sumber surat kabar kontemporer yang terbit di Jakarta dan Semarang serta koleksi pustaka terkait lainnya. Sumber-sumber tersebut diperoleh dari Perpustakaan Nasional dan perpustakaan di daerah setempat. Hasil penelitian menunjukkan bahwa beberapa faktor memengaruhi radikalisme dan militansi pemuda di Semarang. Pertama, motivasi dan tujuan kuat mereka untuk melawan pendudukan tentara Jepang dan kembalinya Sekutu. Kedua, hasil pendidikan Jepang bagi pemuda melalui organisasi militer dan semi-militer selama pendudukan Jepang yang memperkuat mentalitas militer. Ketiga, pengaruh organisasi kelompok pemuda sosialis-Marxis yang berkembang sejak masa pergerakan nasional, sehingga membuat Kota Semarang dikenal sebagai kota “merah”.